Transformasi Digital dan Dampak Fiskal Pengembangan Pariwisata Halal di Indonesia - Kuncoro Budi Riyanto; Indah Purnomowati; Arwan Junianto (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
This study examines the influence of digital transformation on the development of halal tourism in Indonesia and its financial implications for the national economy. The research employs a qualitative descriptive design based on secondary data by analyzing academic literature, government reports, and digital tourism platforms to understand the interaction between digitalization, Muslim tourist behavior, and public financial governance. The findings indicate that the adoption of digital technologies, such as etourism platforms, big data analytics, artificial intelligence, and Islamic financial technology (Islamic fintech) significantly enhances competitiveness, fiscal transparency, and financial inclusion within the halal tourism ecosystem. Digital transformation enables more efficient destination management, improves service responsiveness to the needs of Muslim tourists, and optimizes national and regional revenue generation. The study also confirms the relevance of the Resource Based View (RBV) and Dynamic Capability Theory (DCT) in explaining how digital assets and adaptive capabilities serve as sources of sustainable competitive advantage. Furthermore, government led digital governance integrated with sharia based financial systems has been shown to strengthen fiscal efficiency and promote inclusive economic growth. These developments support the achievement of the Sustainable Development Goals (SDGs) by fostering transparency, inclusivity, and sustainability in Indonesia’s halal tourism and public finance sectors.